The Microtubule Cytoskeleton at the Synapse - Parato, Julie (Neurosci Lett, 2021)
In neurons, microtubules (MTs) provide routes for transport throughout the cell and structural support for dendrites and axons. Both stable and dynamic MTs are necessary for normal neuronal functions. Research in the last two decades has demonstrated that MTs play additional roles in synaptic structure and function in both pre- and postsynaptic elements. Here, we review current knowledge of the functions that MTs perform in excitatory and inhibitory synapses, as well as in the neuromuscular junction and other specialized synapses, and discuss the implications that this knowledge may have in neurological disease